2011
DOI: 10.1007/s11069-011-9898-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of seismicity parameters across India and adjoining areas

Abstract: An attempt has been made to quantify the variability in the seismic activity rate across the whole of India and adjoining areas (0-45°N and 60-105°E) using earthquake database compiled from various sources. Both historical and instrumental data were compiled and the complete catalog of Indian earthquakes till 2010 has been prepared. Region-specific earthquake magnitude scaling relations correlating different magnitude scales were achieved to develop a homogenous earthquake catalog for the region in unified mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…The PHA values for Greater Mumbai region varies from 0.076g to 0.328g. Kolathayar et al (2012) reported the PHA value of 0.27g for Mumbai city which falls within the range obtained in the present study. The probabilistic seismic hazard evaluation by Raghu Kanth and Iyengar (2006) obtained the bedrock level PHA values of 0.09g and 0.18g for a return period of 475 years and 2475 years respectively for Mumbai city.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The PHA values for Greater Mumbai region varies from 0.076g to 0.328g. Kolathayar et al (2012) reported the PHA value of 0.27g for Mumbai city which falls within the range obtained in the present study. The probabilistic seismic hazard evaluation by Raghu Kanth and Iyengar (2006) obtained the bedrock level PHA values of 0.09g and 0.18g for a return period of 475 years and 2475 years respectively for Mumbai city.…”
Section: Resultssupporting
confidence: 91%
“…The results obtained from the present study are compared with IS 1893: Part 1 (2002) and Kolathayar et al (2012). These studies showed uniform hazard distribution for Greater Mumbai region however present study found a comparatively high hazard on the southern part of the study region and confirmed from the recent knowledge of seismic activity and seismic sources in the study region.…”
supporting
confidence: 79%
“…As the moment magnitude (M W ) scale is the most advanced and widely used magnitude scale, the original magnitudes of Indian earthquakes in different time periods have been converted to unified M W magnitudes. Several relations were proposed by different researchers to convert different magnitude scales to M W (Nuttli 1983;Giardini 1984;Kiratzi et al 1985;Heaton et al 1986;Patton and Walter 1993;Johnston 1996;Papazachos et al 1997;Scordilis 2006;Thingbaijam et al 2008;and Kolathayar et al 2011, among many others). Based on the earthquake data available from India and the adjoining area, Kolathayar et al errors and source characters such as stress drop, fault geometry, etc.…”
Section: Homogenization Of the Catalogmentioning
confidence: 99%
“…It is always advisable to use the region-specific magnitude conversion relations (Rui-feng et al 2007). Hence the M W values obtained from the correlations developed by Kolathayar et al (2011) were used for homogenization of different magnitude scales. For the conversion of intensity scale to M W , the relation developed by Menon et al (2010) was used as they have commented that the use of relation suggested by Reiter (1990) to convert the intensity scale to moment magnitude may not hold for Indian conditions.…”
Section: Homogenization Of the Catalogmentioning
confidence: 99%
See 1 more Smart Citation